Organization of network interaction in the educational activities of Elementary School students with dysgraphia in English Lessons - Koreneva, Maryam; Yadrov, Konstantin; Vittenbek, Victor; Ivanova, Galina; Bryantseva, Marina; Poruchkina, Svetlana (Revista Conrado, 2023)
The relevance of the research problem relates to the need to renew the content of professional training of English teachers and educational psychologists for working with children with dysgraphia. Various writing disorders are observed both in writing in the native language (Russian) and in writing in English. The goal of the study is to identify the educational needs of elementary school students with writing disorders in English lessons; to develop and test an individual program of psychological and pedagogical support; to offer practical recommendations for psychological and pedagogical support during pre-letter and letter periods; to create a network map of psychological and pedagogical support in the educational process. Empirical research confirms that the use of the individual program of psychological and pedagogical support of students with dysgraphia by the teacher contributes to the correction of their issues (developing the skills of accurate coherent written expression). Materials of the article will be of interest to practicing English teachers, educational psychologists, neuropsychologists, and university teachers and students exploring the issues of specific correction of difficulties in teaching foreign languages to elementary school students with dysgraphia. Keywords: Graphic skills, educational process, optical dysgraphia, psychological and pedagogical child development, writing disorder. RESUMEN La relevancia del problema de investigación se relaciona con la necesidad de renovar el contenido de la formación profesional de los docentes de inglés y psicopedagogos para el trabajo con niños con disgrafía. Se observan varios trastornos de escritura tanto en la escritura en el idioma nativo (ruso) como en la escritura en inglés. El objetivo del estudio es identificar las necesidades educativas de los estudiantes de primaria con trastornos de escritura en las clases de inglés; desarrollar y probar un programa individual de apoyo psicológico y pedagógico; ofrecer recomendaciones prácticas para el apoyo psicológico y pedagógico durante los períodos de pre-carta y carta; crear un mapa de red de apoyo psicológico y pedagógico en el proceso educativo. La investigación empírica confirma que el uso del programa individual de apoyo psicológico y pedagógico de los estudiantes con disgrafía por parte del maestro contribuye a la corrección de sus problemas (desarrollando las habilidades de expresión escrita precisa y coherente). Los materiales del artículo serán de interés para profesores de inglés en ejercicio, psicólogos educativos, neuropsicólogos y profesores y estudiantes universitarios que exploren los problemas de la corrección específica de las dificultades en la enseñanza de idiomas extranjeros a estudiantes de escuela primaria con disgrafía. Palabras clave: Habilidad gráfica, proceso educativo, disgrafía óptica, desarrollo psicopedagógico infantil, trastorno de la escritura.